2019
DOI: 10.1103/physrevd.100.074021
|View full text |Cite
|
Sign up to set email alerts
|

Extracting a short distance top mass with light grooming

Abstract: We propose a kinematic method based on a factorization formula for precisely measuring the top quark mass m t in pp collisions using boosted top jets with light soft drop grooming. By using light grooming, which is an order of magnitude less aggressive than typical grooming, we retain a universal description of the top-mass scheme and decay effects, while still effectively removing soft contamination from the top jet. We give field theory results for the hadronization corrections for jets induced by a heavy to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 37 publications
2
80
0
Order By: Relevance
“…We note that some of our results are also used in our theoretical analysis of soft drop groomed top quark jets in Ref. [62], where it is pointed out that these hadronization corrections are also universal between massive and massless quarks. While we focused on the case of jet mass in this work, we emphasize that the same techniques can also be applied to other groomed observables such as angularities [82].…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…We note that some of our results are also used in our theoretical analysis of soft drop groomed top quark jets in Ref. [62], where it is pointed out that these hadronization corrections are also universal between massive and massless quarks. While we focused on the case of jet mass in this work, we emphasize that the same techniques can also be applied to other groomed observables such as angularities [82].…”
Section: Resultsmentioning
confidence: 61%
“…Resummation of the soft drop jet mass for top jets was studied in Ref. [62] and e (α) 2 for bottom quarks in Ref. [63].…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we focus on the soft drop grooming algorithm of [4]. Both on the experimental [5][6][7][8] and the theoretical side [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], significant progress has been made recently in improving our understanding of soft drop groomed jet observables. In the heavy-ion community, soft drop groomed jet substructure observables have also received increasing attention from both experiment [25][26][27][28] and theory [29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Developments in jet substructure (see [36] for a recent review) have shown that the modified mass drop tagging algorithm (mMDT) or soft-drop grooming procedure robustly removes contamination from both underlying event and non-global color-correlations, see Refs. [21,22,37], and have been applied to study a wide variety of QCD phenomenology within jets [38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%